Photocatalytic performances and durability of TiO2/cement composites prepared by a smear method for organic wastewater degradation. Issue 17 (1st December 2019) - Feng, Shenglei; Liu, Fanghua; Fu, Xiang; Peng, Xiaoying; Zhu, Jielu; Zeng, Qingli; Song, Junwei
Abstract: Photocatalytic TiO2 /cement composites were prepared by a smear method with a slim thread, through floating TiO2 /waterproof emulsion mixture onto the pre-wet surfaces of cement pastes/mortars. The composition, microstructure, hydrophobicity, photocatalytic properties and durability of the prepared TiO2 /cement composites were systematically studied. The results showed that TiO2 particles were dispersed equally on the surfaces of the cement pastes. The TiO2 /cement paste composites had good hydrophobic property with contact angle of 145.2 ° C. Under UV irradiation, the photocatalytic cement pastes could almost completely degrade 10 mg L −1 Rhodamine B (RhB), methylene blue (MB) and methylene orange (MO) in 50 min. After soaking in acid or alkaline solution, the photocatalytic cement pastes had better degradation performance than before soaking. Good cycling performance was achieved for the photocatalytic cement pastes. In the aspect of durability, the photocatalytic cement mortars had good water permeation resistance, chloride penetration resistance and carbonation resistance.